Secular stagnation and Google Trends: Can we find out what people think? - Katarzyna Schmidt; Mateusz Gajtkowski (Review of Economic Analysis (REA), 2021)
The main aim of the study was to verify the thesis that the US economy is measured against the spectre of secular stagnation by determining the mood of American society using Google Trends. While performing the analysis, the authors used data on the American market for the years 2004-2018. The study comprised 42 entries, including 19 entries from the category 'social' and 23 entries from the category 'financial'. The analyses do not allow for a clear statement that the US economy is facing the spectre of secular stagnation, but they allow us to formulate the observation that the mood of the society is moderately pessimistic, which undoubtedly translates into economic activity and may be the cause of the persisting economic stagnation.
Keywords: E32; E66; E70; 330; secular stagnation; Google Trends; social mood; sentiment